Phosphorylation Affects DNA-Binding of the Senescence-Regulating bZIP Transcription Factor GBF1 - Anja Smykowski; Stefan M. Fischer; Ulrike Zentgraf (Plants, 2015)
Massive changes in the transcriptome of Arabidopsis thaliana during onset and progression of leaf senescence imply a central role for transcription factors. While many transcription factors are themselves up- or down-regulated during senescence, the bZIP transcription factor G-box-binding factor 1 (GBF1/bZIP41) is constitutively expressed in Arabidopsis leaf tissue but at the same time triggers the onset of leaf senescence, suggesting posttranscriptional mechanisms for senescence-specific GBF1 activation. Here we show that GBF1 is phosphorylated by the threonine/serine CASEIN KINASE II (CKII) in vitro and that CKII phosphorylation had a negative effect on GBF1 DNA-binding to G-boxes of two direct target genes, CATALASE2 and RBSCS1a. Phosphorylation mimicry at three serine positions in the basic region of GBF1 also had a negative effect on DNA-binding. Kinase assays revealed that CKII phosphorylates at least one serine in the basic domain but has additional phosphorylation sites outside this domain. Two different ckII α subunit1 and one α subunit2 T-DNA insertion lines showed no visible senescence phenotype, but in all lines the expression of the senescence marker gene SAG12 was remarkably diminished. A model is presented suggesting that senescence-specific GBF1 activation might be achieved by lowering the phosphorylation of GBF1 by CKII.